Relationship Of Worm Infection And Hemoglobin Levels To Stunting In Toddlers Aged 3-5 Years In Indramayu - asa azkatu razaq; Moesijanti Y.E. Soekatri (Politeknik Kesehatan Kemenkes Jakarta II, 2022)
The incidence of anemia is not only caused by iron deficiency, but also because of infestation disease such as worms. Worms are attached in human intestinal mucosa that will absorb blood and its nutrients, causing blood deficiency. This study aims to find out the relationship between worm infection and hemoglobin levels to stunting among toddlers aged 3-5 years in Indramayu. This research is cross-sectional study, the total subjects were 35 children selected using purposive sampling technique living at working area of Puskesmas Eretan. Data collected were worm eggs in feces, then placed in a stool and examined using microscopic test. Hemoglobin levels and stunting were determined by using Hb meter and microtoice tools, respectively. Stunting was analyzed using Height for Age The results showed that in all subjects, there was no worm eggs found in their feces. The percentage of stunting children who had Hb ≥ 11 gr/dl were 8,4%. There was no relationship between hemoglobin levels and stunting using Fisher’s exact test (p>0.05).